All ptomaines fault! : The strange story of the cadaveric alkaloids, from forensic medicine to molecular biology passing through the asylum. - Donato, Francesca; Greco, Rossella; Carpentieri , Carlotta; Pittore, Benedetta; D'Orlando, Carmela; Donato, Annalidia; Malara , Natalia; Donato, Giuseppe (Medicina Historica, 2022)
This essay attempts to reconstruct the story of ptomaines, discovered in 1872 by the Italian chemist Francesco Selmi. This work provides a brief summary of this story, focusing also on an emblematic clinical study by the end of the 19th century, written by Raffaele Canger, a doctor who worked in the Asylum of Nocera Inferiore in Italy.The main thesis of Canger's paper is that the transient neuropsychiatric symptoms, which can occur during influenza or other infectious diseases, are due to a toxic delirium caused by the direct action of ptomaines on the brain with subsequent restitutio ad integrum.The importance of the discovery of ptomaines was discredited for a very long time, but recently, with the contribute of molecular biology it was established again the role of these molecules in human pathology.